Highly Chemoselective Transamidation of Unactivated Tertiary Amides by Electrophilic N−C(O) Activation by Amide‐to‐Acyl Iodide Re‐routing. Issue 24 (11th April 2022) - Zuo, Dongxu; Wang, Qun; Liu, Long; Huang, Tianzeng; Szostak, Michal; Chen, Tieqiao
Abstract: The challenging transamidation of unactivated tertiary amides has been accomplished via cooperative acid/iodide catalysis. Most crucially, the method provides a novel manifold to re‐route the reactivity of unactivated N, N‐dialkyl amides through reactive acyl iodide intermediates, thus reverting the classical order of reactivity of carboxylic acid derivatives. This method provides a direct route to amide‐to‐amide bond interconversion with excellent chemoselectivity using equivalent amounts of amines. The combination of acid and iodide has been identified as the essential factor to activate the amide C−N bond through electrophilic catalytic activation, enabling the production of new desired transamidated products with wide substrate scope of both unactivated amides and amines, including late‐stage functionalization of complex APIs (>80 examples). We anticipate that this powerful activation mode of unactivated amide bonds will find broad‐ranging applications in chemical synthesis. Abstract : The challenging transamidation of unactivated tertiary amides using equivalent amounts of amines has been accomplished via cooperative acid/iodide catalysis. The method provides a novel manifold to re‐route the reactivity of unactivated and unreactive N, N ‐dialkyl amides through reactive acyl iodide intermediates, representing a powerful new activation mode of unactivated amide bonds.